Preparation of Zinc-Sulfide Thin Films in the Presence of Sodium Tartrate as a complexing agent - Anuar, Kassim; Zainal, Zulkarnain; Nagalingam, Saravanan; N., Asikin (2008)

(untitled)
The article offers information on the experiment done for the electrodeposition of zinc-sulfide (ZnS) thin films on the titanium substrate in the presence of sodium tartrate as a complexing agent. It states that the electrodeposition process has several advantages such as the possibility for large-scale production and minimum waste of components. It mentions that depositions were carried out by varying the deposition potential to determine the optimal conditions of deposition of ZnS thin films